Chronic low back pain in Malaysia: overview of the current practice and future direction - Mohamed, Rozilah @ Abdul Hadi; Aziz, Ahmad Akmal; Mohamed Zaini, Mohamed Asri (Malaysian Society of Anaesthesiologist, 2021)
Low back pain is one of the most common presentations of pain with prevalence in about 12% of adults in Malaysia, with direct impact on economic burden towards a country. Lumbar facet joint arthropathy constitutes the most common type of back pain, followed by sacroiliac joint arthropathy. Among the approaches which are currently available in managing back pain are multimodal analgesics, cognitive behavioural therapy, and interventional pain procedures. The purpose of this review is to describe the incidence and approaches in management of low back pain available in Malaysia, and its future direction.